DETERMINANTS OF LOCAL TAXES: EVIDENCE FROM TULUNGAGUNG - Nurul Mazidah; Muhammad Syahrul Hidayat; Ika Puspitasari; Mugiyati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
Improvements in public welfare, quality of life, and access to services such as education, healthcare, infrastructure, transparency, accountability, and community participation in local policy formulation measure the success of decentralization in Indonesia. This study aims to analyze the factors influencing local tax revenues as an indicator of fiscal decentralization success in Tulungagung Regency. Applying the Error Correction Model (ECM), this research examines both the long-term and short-term relationships between population growth, income levels, and socio-economic development on local tax revenues. As a result, this study indicates that all variables have a significant impact on local tax revenues. The population growth coefficient of 0,034416 suggests that a 1% increase in population contributes to higher local tax revenues. The income level coefficient of 0,092312 signifies that rising income levels enhance tax capacity. Meanwhile, socio-economic development has the most substantial effect, with a coefficient of 0,231872. Reflecting the improvements in public welfare directly contributes to increased local tax revenues. Accordingly, this study reveals that the trend of local tax revenues in Tulungagung has increased dramatically from 2011 to 2023, demonstrating the effectiveness of regional fiscal policies. This research contributes to supporting local budgetary policy based on strengthening socio-economic factors as a strategy to increase local tax revenue.